Volumetric and cortical thickness alterations in alcohol dependence: evidence of accelerated brain aging and clinical correlations - Çınaroğlu, Metin; Yılmazer, Eda; Ülker, Selami Varol; Taçyıldız, Kerime; Tarlacı, Sultan (Frontiers in Psychiatry, 2025)
BackgroundChronic alcohol dependence is associated with structural brain changes that resemble premature aging, particularly in frontal, parietal, and subcortical regions. This study examined brain volume, cortical thickness, and brain-predicted age in individuals with alcohol dependence and assessed associations with clinical symptoms.MethodsThirty-one alcohol-dependent patients (mean age = 37.8 ± 7.3 years) and 26 age-matched healthy controls (mean age = 35.0 ± 8.5 years) underwent high-resolution T1-weighted MRI scanning. Brain structural analyses, including regional volumetry and cortical thickness estimation, were conducted using the validated volBrain platform. The system also provided individualized brain-predicted age estimates via its machine learning-based Brain Structure Ages (BSA) pipeline. Clinical assessments included the Michigan Alcoholism Screening Test (MATT), Penn Alcohol Craving Scale (PENN), Beck Depression and Anxiety Inventories (BDI-II, BAI), and detailed alcohol use history.ResultsAlcohol-dependent participants showed significant reductions in total white matter, right frontal lobe, inferior frontal gyrus, bilateral postcentral gyri, and left superior occipital gyrus volumes (p < 0.05), along with widespread cortical thinning. Brain-predicted age was on average 11.5 years greater in patients than in controls (p < 0.001), especially in white matter and basal ganglia structures. Higher MATT scores correlated with reduced right precentral gyrus and left caudate volumes. PENN scores were positively associated with occipital volumes; however, this association weakened after controlling for age. Depression was linked to reduced frontal pole and increased amygdala volume, while anxiety was associated with smaller orbitofrontal and angular gyrus volumes.ConclusionsAlcohol dependence is marked by diffuse brain atrophy and accelerated brain aging. Structural alterations correspond to addiction severity, craving, and mood symptoms, highlighting brain-predicted age as a potential biomarker of cumulative alcohol-related neurodegeneration.